Identifikasi dan Karakterisasi Senyawa Bioaktif Antikanker dari Ekstrak Etanol Kulit Batang Kayu Bitti (Vitex cofassus) - Nuraini Nuraini; Asriani Ilyas; Iin Novianty (Al-Kimia, 2015)
Bitti wood (Vitex cofassus) is one of the plants in Verbenaceae family and known by the people of South Sulawesi as the building material. The aims of this research  is to identify and characterize  the anticancer bioactive compound in ethanol extract of vortex Bitti wood (Vitex cofassus) and to determine the bioactivity value. This research uses extraction and fraction method, identification uses thin layer chromatography (TLC) and phytochemical test to know metabolism secunder and characterization with FTIR. The result from isolation shows that the amorf shape with 18 mg has white and yellow colour. The purification is conduted by using spectroscopy test FTIR. The result shows that the crystal has flavonoids compound which is solid with phytochemical test like positive product by using FeCl3 5%, NaOH 10% and H2SO4 P. Thick extract, fraction combination and amorf continued with toxicity test with the animal test Artemia salina Leach it uses Brine Shrimp Lethality test (BST) method. LC50 value which is gotten the three samples is thick extract 29,51 ppm, combination fraction 169,82 ppm and amorf 562,34 ppm.